A novel regenerative endodontic procedure in a traumatized immature tooth using amniotic membrane - Ellana Jermiah Joseph; Mahabala Y Karuna; Arathi Rao; Ashwin Rao; Anupama P Nayak (Wolters Kluwer Medknow Publications, 2021)
Tooth nonvitality is one of the frequently seen consequences of dental trauma that causes the arrest of root development. Amniotic membrane has received a lot of attention for its use in transplantation and regeneration procedures. This article reports a unique and novel case of successful regenerative endodontic procedure done using amniotic membrane in a traumatized immature right maxillary central incisor of an 8-year-old girl. The clinical and radiographic evaluation done during the recall visits at 1, 3, 6, 9 and 12 months showed a progressive root growth with apical closure.